Intrusiveness and data protection in iot solutions for smart homes. amfiteatru - Irina Maiorescu; Larisa Gabudeanu; Alexandru-Lucian Vîlcea; Gabriel-Cristian Sabou; Marian Dârdală (Amfiteatru Economic Journal, 2021)
The use of Internet of Things devices (IoT) by individuals in their homes has led to new opportunities for companies, to adapt their products, services and offers, based on the user profile. At the same time, these new services involve the reinterpretation of existing requirements regarding data protection, especially in terms of the ethics of using data and the security of personal data. The paper analyses in the scientific literature the intrusiveness generated by aggregations of personal data, the responsibility for data protection and user's perception of these issues. It presents further the results of a quantitative research on 183 respondents of all genders and working in different sectors of activity, with the aim of assessing the perception of intrusiveness and data protection in the use of their smart devices, with potential for IoT home interconnection. The results provide a new perspective on how smart device users relate to key issues from European data protection legislation. The study shows that there are differences explained by gender, age and parental status in the perception of intrusiveness and responsibilities for ensuring the security of aggregated data through IoT solutions. The results also show that accessing certain types of data is perceived as being more intrusive than others, and that respondents rely on other users' reviews to learn how data protection is provided through the IoT device.
Keywords: L86; M31; N44; 330; Internet of Things (IoT); GDPR; smart homes; smart devices; intrusiveness; data protection; data security